LHS1 and SIL1 provide a lumenal function that is essential for protein translocation into the endoplasmic reticulum - Tyson, John R. (Oxford University Press, 2000)
Lhs1p is an Hsp70-related chaperone localized in the endoplasmic reticulum (ER) lumen. Δlhs1 mutant cells are viable but are constitutively induced for the unfolded protein response (UPR). Here, we demonstrate a severe growth defect in Δire1Δlhs1 double mutant cells in which the UPR can no longer be induced. In addition, we have identified a UPR- regulated gene, SIL1, whose overexpression is sufficient to suppress the Δire1Δlhs1 growth defect. SIL1 encodes an ER-localized protein that interacts directly with the ATPase domain of Kar2p (BiP), suggesting some role in modulating the activity of this vital chaperone. SIL1 is a non-essential gene but the Δlhs1Δsil1 double mutation is lethal and correlates with a complete block of protein translocation into the ER. We conclude that the IRE1-dependent induction of SIL1 is a vital adaptation in Δlhs1 cells, and that the activities associated with the Lhs1 and Sil1 proteins constitute an essential function required for protein translocation into the ER. The Sil1 protein appears widespread amongst eukaryotes, with homologues in Yarrowia lipolytica (Sls1p), Drosophila and mammals.